2014
DOI: 10.1016/j.virol.2014.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus infection requires the TSG101 component of the ESCRT machinery

Abstract: Infection with human papillomaviruses (HPV) requires the minor capsid component L2, which plays an essential role in directing appropriate endosomal trafficking. Previous studies have indicated an infection route involving multi-vesicular bodies (MVBs), and an essential element in their biogenesis is the ESCRT machinery. Here we show that the ESCRT component TSG101 is required for optimal infection with both HPV-16 and BPV-1, with loss of TSG101 resulting in a decrease in viral infection, whereas overexpressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 37 publications
3
39
0
Order By: Relevance
“…The transit of vesicles to the TGN and nuclear entry probably involves movement along microtubules by way of molecular motors, since L2 has been shown to interact with dynein [25], while a membrane-associated cellular protease g-secretase is required for localization of L2 and viral DNA to the Golgi apparatus and endoplasmic reticulum [17,26]. It is becoming clear that extensive cellular cargo sorting machinery is involved in L2-related HPV trafficking from endosomes to the nucleus, including SNX17 [21] and SNX27 [27], retromer proteins [23], and at least one member of the ESCRT complex, TSG101 [28]. The exact sequence of events in which HPVs utilize members of the host sorting machinery for the transition to TGN and nucleus remains an important question.…”
Section: Introductionmentioning
confidence: 99%
“…The transit of vesicles to the TGN and nuclear entry probably involves movement along microtubules by way of molecular motors, since L2 has been shown to interact with dynein [25], while a membrane-associated cellular protease g-secretase is required for localization of L2 and viral DNA to the Golgi apparatus and endoplasmic reticulum [17,26]. It is becoming clear that extensive cellular cargo sorting machinery is involved in L2-related HPV trafficking from endosomes to the nucleus, including SNX17 [21] and SNX27 [27], retromer proteins [23], and at least one member of the ESCRT complex, TSG101 [28]. The exact sequence of events in which HPVs utilize members of the host sorting machinery for the transition to TGN and nucleus remains an important question.…”
Section: Introductionmentioning
confidence: 99%
“…DiGiuseppe and coworkers revealed that L2 amino acid residues 64 to 81 and 163 to 170 and the L2 C-terminal exposure on the cytosolic side of intracellular membranes enable interaction with cytosolic host cell factors (39). Interactions of L2 with actin (40), components of the retrograde transport machinery (37,41,42), sorting nexins 17 and 27, TSG101, ␥-secretase, and Hsc70, as well as the microtubule network, have been reported (37,(41)(42)(43)(44)(45)(46)(47)(48). These interactions result in trafficking to the Golgi network (37,41,42,47), transport toward the nucleus (43,44), and accumulation at nuclear substructures (49)(50)(51)(52)(53).…”
mentioning
confidence: 99%
“…Previous studies had shown that the ESCRT component TSG101 and ESCRT-associated ALIX were required for infectious entry of HPV-163031. We were interested first in investigating whether the ESCRT machinery was required for infection with other papillomavirus (PV) types and, further, how the ESCRT machinery might play a role in this process.…”
Section: Resultsmentioning
confidence: 99%
“…To do this we made use of the Pseudovirion (PsVs) system, where L1 and L2 are assembled into PsVs in HEK293TT cells and package a luciferase reporter plasmid35. In this study we used HPV-16, HPV-5, BPV-1, MmuPV-1 and SfPV-1, and as a control we also included Merkel Cell Polyomavirus (MCPyV) in the assays, which in our previous assays was found to be unaffected by TSG101 depletion30. HaCaT cells were first transfected with siRNAs against TSG101, VPS4A, VPS4B and HRS and after 72 h the cells were infected with the different PsVs containing luciferase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation